2021
DOI: 10.1016/j.isci.2021.103486
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for chemical vapor deposition of two-dimensional organic-inorganic halide perovskites

Abstract: Summary Two-dimensional (2D) organic-inorganic halide perovskites (OIHPs) with an alternating stacked structure of an organic layer and an inorganic layer draw significant attention for photovoltaics, multiple quantum-well, and passivation of three-dimensional perovskites. Although the low-cost and simple spin-coating process of these materials offers a vast platform to study fundamental properties and help them achieve rapid progress in electronics and optoelectronics, chemical vapor deposition (CV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…At high temperatures (regime IV), we believe that the surface diffusion of atoms is sufficiently high that the additional adatoms always find energetically favored lateral sites much faster than adding van der Waals layers, leading to NPL growth (Figure B). This is a case similar to the closed-reactor syntheses that tend to produce thermodynamic products . On the other hand, at intermediate temperatures (regime III), surface species are less mobile, and thus, the lateral and vertical growth rates are comparable, leading to isotropic three-dimensional growth of crystalline nuclei into pyramidal shapes, as shown in the inset of Figure C.…”
Section: Resultsmentioning
confidence: 78%
“…At high temperatures (regime IV), we believe that the surface diffusion of atoms is sufficiently high that the additional adatoms always find energetically favored lateral sites much faster than adding van der Waals layers, leading to NPL growth (Figure B). This is a case similar to the closed-reactor syntheses that tend to produce thermodynamic products . On the other hand, at intermediate temperatures (regime III), surface species are less mobile, and thus, the lateral and vertical growth rates are comparable, leading to isotropic three-dimensional growth of crystalline nuclei into pyramidal shapes, as shown in the inset of Figure C.…”
Section: Resultsmentioning
confidence: 78%
“…A single-step CVD process has been reported for the deposition of 2D BA 2 PbI 4 and PEA 2 SnI 4 microplates. 30 Due to the challenges related to the difference in the sublimation temperatures of the different precursor materials in powder form, this single-step route is not ideal for conformal deposition of a compact and uniform 2D-HHP thin film. To mitigate this challenge, we use a two-step CVD protocol similar to our prior work on MAPbI 3 thin films with improved air-and temperature stability.…”
Section: Resultsmentioning
confidence: 99%
“…We note these are continuous films and the overall thickness of the converted perovskite layer is higher compared to CVD-grown flakes. 30 The three samples having different film thicknesses were investigated by XRD using an image plate to collect the data while the angle of incidence with respect to the surface was varied continuously from 2°to 25°, as discussed in the methods section. Figure 7a shows the diffraction images from all three samples.…”
Section: Orientation Properties Of the Perovskite Planesmentioning
confidence: 99%
“…In addition, we have shown that CVD offers the advantage of an improved environmental stability of 3D OIHP layers and control of the phase stability of the material . A one-step CVD process has been reported for the growth of 2D Sn-only perovskite [(PEA) 2 SnI 4 ] . Although simpler, this one-step CVD process will be difficult to apply for the deposition of 2D Sn–Pb compound perovskites because it requires simultaneous sublimation of the organic cation and the Pb and Sn halide sources.…”
Section: Introductionmentioning
confidence: 99%
“…45 A one-step CVD process has been reported for the growth of 2D Sn-only perovskite [(PEA) 2 SnI 4 ]. 42 Although simpler, this one-step CVD process will be difficult to apply for the deposition of 2D Sn−Pb compound perovskites because it requires simultaneous sublimation of the organic cation and the Pb and Sn halide sources. Considering the benefits of CVD, it is surprising there is no literature on the CVD of Sn− Pb compound perovskite materials (to the best of our knowledge).…”
Section: Introductionmentioning
confidence: 99%